Utilization of Plant Derived Metallic Nanoparticles for Biomedical Applications - Sharma, Akanksha; Sharma, Pramod K.; Malviya, Rishabha (Natural Products Journal, The, 2021)
Aim: The aim of the manuscript is to summarize various biomedical applications of metallic nanoparticles that are synthesized using herbal components. Methodology: Various search engines such as google, sciencedirect, scopus etc. were utilized for the literature survey. The literature survey was focused on the different parts of plants like leaves, stem, root, fruit and flowers as a source of therapeutic active component and their utilization in the preparation of metallic nanoparticles. Manuscript also described in depth information about the different activities of synthesized nanoparticles. It was concluded from the literature surveys that, a plant extract used for the synthesis of metallic nanoparticles was cheaper than the synthetic chemicals and less toxic to the environment. Results and Conclusion: The plant extract used in the synthesis is herbal in nature. It does not cause any environmental hazards. Instead of synthetic chemicals, the plant extracts which are used in the synthesis of metallic nanoparticles, act as capping, reducing and stabilizing agent during the synthesis. It was also observed that plant-based metallic nanoparticles were more stable, the synthesis rate was faster as compared to chemical processes and can be easily obtained in different shapes and sizes.
Keywords: Plant based nanoparticles